Characterization of feline mandibular angle fractures utilizing in silico model construction and fracture mapping - Tu, Tsung-Han; Hetzel, Scott J.; Soukup, Jason W. (Frontiers in Veterinary Science, 2025)
IntroductionThe unique and dynamic features of the feline mandibular angle make open reduction and internal fixation in this region more challenging than in the mandibular body. Visualization of fracture patterns through a fracture map can be a valuable tool for qualitative analysis of fractures in this region. In addition, fracture maps are useful in designing hardware for rigid internal fixation. The primary aim of this study was to identify possible associations between patient demographics, fracture etiologies, and fracture patterns affecting the feline mandibular angle. The secondary aim was to create fracture maps to qualitatively characterize fracture patterns.MethodsNineteen cats with 22 mandibular angle fractures were included in this retrospective study. Medical records were reviewed and statistically analyzed. Fracture maps were created using three-dimensional in silico models derived from computed tomographic images and analyzed based on fracture categories/features (simple vs. comminuted fractures, fracture etiologies, bilateral fractures, and age).ResultsNo significant associations were found between dependent variables (fracture type, dorsal fracture location/fracture origin, ventral fracture location/fracture termination, mandibular foramen involvement, and displacement score) and independent variables (age, sex, and etiology). Fracture maps provided important qualitative information that was not evident from statistical analysis of patient demographics/fracture characteristics.DiscussionWe conclude that in silico evaluation of fracture patterns provides important qualitative information that could not be obtain by traditional fracture characterization. In addition, the unique morphologic features of the feline mandibular angle likely play a significant role in fracture mechanics and fracture patterns.